Stereoselective Synthesis of Highly Functionalized Hydroindoles as Building Blocks for Rostratins B–D and Synthesis of the Pentacyclic Core of Rostratin C. Issue 31 (14th July 2015) - Zhong, Sabilla; Sauter, Paul F.; Nieger, Martin; Bräse , Stefan
Abstract The stereoselective synthesis of a variety of functionalized hydroindoles suitable as building blocks for thiodiketopiperazine natural products such as rostratins B–D is reported. The key precursor for all transformations is a previously reported hexahydroindole compound. All functional groups were installed with the desired stereochemistry and the feasibility of the synthetic strategy was exemplified by dimerization of two hydroindole units to form the pentacyclic C2‐symmetric scaffold of rostratin C.